Lyman Potter Spencer papers - Spencer, Lyman Potter, 1840-1915.
Correspondence, diaries, notebooks, account books, genealogical file, penmanship file, and other papers documenting Spencer's Civil War service with the 2nd Ohio Heavy Artillery Regiment and his efforts to continue the publication of the copybooks begun by his father, Platt R. Spencer, who developed the Spencerian style of handwriting. Penmanship files reflect Lyman Potter Spencer's progress as an artist and calligrapher. Includes material relating to Platt R. Spencer and to other members of the Spencer family. Correspondents include Hamilton Fish and James A. Garfield.
Artist, soldier, and calligrapher.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Fish, Hamilton, -- 1808-1893 -- Correspondence; Garfield, James A. -- 1831-1881 -- Correspondence; Spencer, Platt R. -- 1800-1864.; Spencer family; United States. -- Army. -- Ohio Heavy Artillery Regiment, 2nd (1863-1865); Art, American; Calligraphy; Copybooks; Penmanship; Ohio -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; Artists; Calligraphers; Soldiers